Pneumococcal and Legionella Urinary Antigen Tests in Community-acquired Pneumonia: Prospective Evaluation of Indications for Testing. (28th September 2018) - Bellew, Shawna; Grijalva, Carlos G; Williams, Derek J; Anderson, Evan J; Wunderink, Richard G; Zhu, Yuwei; Waterer, Grant W; Bramley, Anna M; Jain, Seema; Edwards, Kathryn M; Self, Wesley H
Abstract: Background: Adult, community-acquired pneumonia (CAP) guidelines from the Infectious Diseases Society of America (IDSA) and American Thoracic Society (ATS) include indications for urinary antigen tests (UATs) for Streptococcus pneumoniae (SP) and Legionella pneumophila (LP). These recommendations were based on expert opinions and have not been rigorously evaluated. Methods: We used data from a multicenter, prospective, surveillance study of adults hospitalized with CAP to evaluate the sensitivity and specificity of the IDSA/ATS UAT indications for identifying patients who test positive. SP and LP UATs were completed on all included patients. Separate analyses were completed for SP and LP, using 2-by-2 contingency tables, comparing the IDSA/ATS indications (UAT recommended vs not recommended) and UAT results (positive vs negative). Additionally, logistic regression was used to evaluate the association of each individual criterion in the IDSA/ATS indications with positive UAT results. Results: Among 1941 patients, UATs were positive for SP in 81 (4.2%) and for LP in 32 (1.6%). IDSA/ATS indications had 61% sensitivity (95% confidence interval [CI] 49–71%) and 39% specificity (95% CI 37–41%) for SP, and 63% sensitivity (95% CI 44–79%) and 35% specificity (95% CI 33–37%) for LP. No clinical characteristics were strongly associated with positive SP UATs, while features associated with positive LP UATs were hyponatremia, fever, diarrhea, and recent travel. Conclusions: Recommended indications for SP and LP urinary antigen testing in the IDSA/ATS CAP guidelines have poor sensitivity and specificity for identifying patients with positive tests; future CAP guidelines should consider other strategies for determining which patients should undergo urinary antigen testing. Abstract : The recommended criteria from the Infectious Diseases Society of America and American Thoracic Society community-acquired pneumonia guidelines regarding which patients should undergo pneumococcal and Legionella urinary antigen tests have poor sensitivity and specificity for detection of these pathogens.